Preoperative Computed Tomography Angiography for ALT Flaps Optimizes Design and Reduces Operative Time - Schneider, Christopher M.; Palines, Patrick A.; Womac, Daniel J.; Tuggle, Charles T.; St Hilaire, Hugo; Stalder, Mark W. (Journal of Reconstructive Microsurgery, 2021)
Background Computed tomography angiography (CTA) has been widely used for perforator mapping in abdominal-based reconstruction, but it is less widespread in the anterolateral thigh (ALT) flap. However, CTA may be quite useful for ALT planning, as this flap has demonstrated substantial variability in intrapatient bilateral vascular anatomy. This study investigated whether standard use of preoperative CTA resulted in selection of the donor extremity with preferential perforator anatomy, and whether this affected operative time and postoperative outcomes.Methods A retrospective review of 105 patients who underwent proposed ALT flap reconstruction was performed. Seventy-nine patients received bilateral lower extremity CTAs, which were evaluated for dominant perforator anatomy (septocutaneous, musculoseptocutaneous, or musculocutaneous). Donor extremity selection was noted, and predicted perforator anatomy was compared with that encountered intraoperatively.Results Among the 73 patients who received bilateral imaging and ultimately received an ALT, congruent findings between imaging and surgical exploration were observed in 51 (69.8%) patients. Thirty (37.9%) patients had asymmetric perforator anatomy between their bilateral extremities on imaging. Among these, the leg with optimal perforator anatomy was selected in 70% of cases. There were no significant reductions among postoperative complication rates, but selection of the donor site with preferential anatomy was associated with a decrease in operative time (p = 0.049) among patients undergoing extremity reconstruction.Conclusion CTA is a useful tool for optimizing donor site selection for ALT flaps and reducing operative time. We believe that standard use of preoperative CTA in ALTs warrants further consideration.
Keywords: CTA; ALT flap; perforators